Her American Dream: Bringing Gender Into Institutional-Anomie Theory. (January 2015) - Applin, Samantha; Messner, Steven F.
The purpose of this article is to present a gender-sensitized approach to Institutional-Anomie Theory (IAT) that recognizes the pervasiveness and import of gender at the institutional and cultural levels. Drawing on feminist literature, we discuss the gendering of the family and the economy, and the implications of such gendering for understanding the social organization of American society and the "institutional balance of power, " as explicated by Messner and Rosenfeld in Crime and the American Dream . At a cultural level, we propose that the tendency to conceive of men as normative helps reconcile two seemingly incompatible premises in IAT: the claim that there is a dominant form of social organization that characterizes American society and the empirical observation that cultural orientations and institutional involvement actually differ dramatically for males and females. From a social structural perspective, we describe the varying ways that institutions are by their very nature gendered and how the gendering of institutions can promote and sustain economic dominance—a particularly criminogenic institutional order. Based on these insights, we conclude by proposing some testable hypotheses about the interconnections among gender stratification, institutional structure, and societal levels of crime.